Records of Hero Stone in Sangam Literature - K, Devibooma (International Research Journal of Tamil, 2022)
News about transplantation in Sangam literature is widely included in all texts. Nadukal (stele) performed his heroic deeds in the war, understood the war and was taken to the chest-wounded dead. The article makes it clear that the primary reason for the transplant was that Yathen was in a position to give the impression that the dead were living with them. The article goes on to explain that the performance of Nadukal worship is an expression of heroism and is considered to be the primary debt paid by the warriors to the Veeramanaram Eidyas. The article is located in the Sangam literature to illustrate the way in which Nadukal has continued in Tamil culture for a long time.